Approximate Optimization Study of Light Curing Waterborne Polyurethane Materials for the Construction of 3D Printed Cytocompatible Cartilage Scaffolds - Yi-Wen Chen (MDPI AG, 2021)
Articular cartilage, which is a white transparent tissue with 1–2 mm thickness, is located in the interface between the two hard bones. The main functions of articular cartilage are stress transmission, absorption, and friction reduction. The cartilage cannot be repaired and regenerated once it has been damaged, and it needs to be replaced by artificial joints. Many approaches, such as artificial joint replacement, hyaluronic acid injection, microfracture surgery and cartilage tissue engineering have been applied in clinical treatment. Basically, some of these approaches are foreign material implantation for joint replacement to reach the goal of pain reduction and mechanism support. This study demonstrated another frontier in the research of cartilage reconstruction by applying regeneration medicine additive manufacturing (3D Printing) and stem cell technology. Light curing materials have been modified and tested to be printable and cytocompatible for stem cells in this research. Design of experiments (DOE) is adapted in this investigation to search for the optimal manufacturing parameter for biocompatible scaffold fabrication and stem cell attachment and growth. Based on the results, an optimal working process of biocompatible and printable scaffolds for cartilage regeneration is reported. We expect this study will facilitate the development of cartilage tissue engineering.